Arsenic-induced circASXL1 regulates 16HBE cell proliferation through the P65 signaling axis - Xuefei Yang; Jingwen Tan; Ruihuan Zhao; Tingzhi Duan; Jingchao Yang; Bin Chen; Xinda Yang; Jinhua Wang; Chenglan Jiang; Guanghui Ni; Yanliang Zhang; Yuefeng He (Ecotoxicology and Environmental Safety)
Arsenic is a well-known environmental toxicant, strongly associated with severe toxicity across multiple organs, including the lungs. Circular RNAs (circRNAs) are critical in various cellular processes and linked to disease due to their highly stable covalent closed-loop structure, making them potential therapeutic targets. This study aimed to investigate the expression of circASXL1 under arsenic exposure and its role in 16HBE cell proliferation upon circASXL1 knockdown. Treatment with sodium arsenite increased circASXL1 expression in 16HBE cells, while metabolites had no effect. Notably, circASXL1 knockdown enhanced cell viability and proliferation, concomitant with coordinated activation of STAT3 and P65. Although the precise mechanism requires further validation, our Western blot analyses suggested that STAT3 activation may promote P65 transcriptional activity, as evidenced by upregulated expression of its downstream targets PCNA, BCL2, BCL-XL, and CIAP1. Intriguingly, combinatorial treatment with arsenic and circASXL1-specific siRNAs attenuated both cell proliferation and P65 activation. Our findings propose that arsenic modulates circASXL1 to engage STAT3-P65 crosstalk. This study establishes the arsenic-circASXL1 axis as a novel regulator of STAT3/P65 signaling networks, providing mechanistic insights for combating arsenic-induced pulmonary pathologies.